Renal and hematologic side effects of long‐term intravenous immunoglobulin therapy in patients with neurologic disorders. Issue 6 (30th May 2017) - Levine, Aidan A.; Levine, Todd D.; Clarke, Kathie; Saperstein, David
ABSTRACT: Introduction: For patients receiving intravenous immunoglobulin (IVIg), renal and hemolytic side effects are well recognized. However, there are very few data on the effects of chronic IVIg therapy. Methods: We retrospectively analyzed laboratory data on 166 patients who received IVIg for 12 months with a dose range of 0.441–2.58 g/kg/month, measuring changes in hematocrit and glomerular filtration (GFR) rates at 6 and 12 months. Results: Of the 2, 232 infusions, there were no incidents of clinical hemolysis. However, after 12 months of treatment, 21% of patients had a ≥3‐g/dl decline in hematocrit and 10% had a ≥20% decline in GFR. Discussion: No clinically significant hemolysis was observed in patients receiving chronic IVIg therapy. However, a significant number of patients had a decline in hematocrit and/or GFR while on therapy. This emphasizes the need for observation of hematologic and renal function in patients treated with chronic IVIg. Muscle Nerve 56 : 1173–1176, 2017